2006
DOI: 10.1080/01926230500519824
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death not Related to Coronary Atherosclerosis

Abstract: Sudden cardiac death (SCD) accounts for approximately 300,000 cardiac events in the United States each year, representing an overall incidence of 0.1-0.2% per year. Although the vast majority of these may be attributed to coronary atherosclerosis, a wide variety of nonatherosclerotic-related cardiac diseases have been associated with SCD. This review highlights three general categories of cardiac disease not related to atherosclerosis: the cardiomyopathies, inflammatory myocardial diseases, and ion channel dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
3
10
0
Order By: Relevance
“…Sudden cardiac death (SCD) is one of the leading causes of death in all industrialized countries, with a survival index below 5% in Western Europe. Nearly 80% of these deaths are caused by malignant ventricular tachyarrhythmia, such as ventricular tachycardia or ventricular fibrillation induced by intense ischemic events, in particular as a consequence of myocardial infarction (Arzamendi et al, ; Ladich, Virmani, & Burke, ). Implantable cardioverter defibrillators (ICDs) are heart monitors that are placed under the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden cardiac death (SCD) is one of the leading causes of death in all industrialized countries, with a survival index below 5% in Western Europe. Nearly 80% of these deaths are caused by malignant ventricular tachyarrhythmia, such as ventricular tachycardia or ventricular fibrillation induced by intense ischemic events, in particular as a consequence of myocardial infarction (Arzamendi et al, ; Ladich, Virmani, & Burke, ). Implantable cardioverter defibrillators (ICDs) are heart monitors that are placed under the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of the autopsy pathologist is to reason out the most appropriate cause of the death and to see possibility of toxic drugs and other unnatural deaths. [5] Most of the literature [6][7][8][9][10][11][12][13][14][15][16][17][18] reveals cardiovascular diseases as the common cause. Sequential autopsy examination in sudden death investigation was suggested by Sheppard et al The first step is to consider natural death, followed by exclusion of noncardiac natural death-like hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…We may have included a few patients with other causes of cardiac arrest like pulmonary embolism, dissection, etc. However, these patients represented a very small percentage since the literature review revealed that the predominant cause of sudden cardiac arrest is coronary disease 20 22. We have used criteria known to be associated with acute myocardial infarction and excluded other evident causes of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%